SIMULASI METODE PENUGASAN DAN TRANSPORTASI UNTUK PEMBELAJARAN RISET OPERASIONAL BERBASIS WEB - Satria Juliawan, Komang Gede; Mahendra Darmawiguna, I Gede; Windu Antara Kesiman, Made (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2014)
Operations research is aseries of analysis and mathematical modeling fordecision-making purposes. Assignment andtransportation method was used in this operationsresearch. Assignment method is the method usedto allocate tasks optimally, whether it is in theterm of maximization or minimization.Transportation method is the method used todistribute goods from sources of supply todestinations to get a shipping cost as minimum aspossible. Web assignment and transportationmethod is a method designed to help the users towork in the assignment or transportation. The aimof this study was to design and implement anapplication that could do the calculation ofassignment or transportation method by providinga way of assignment or calculation method oftransportation to find the optimum results.The web-page development ofassignment and transportation method used themodel of ADDIE (Analysis, Design,Development, Implementation, and Evaluation).The developed web-page consists of four menusinclude beranda, penugasan, transportasi andtentang.The results of this research show that thedesign and the implementation of assignment andtransportation method’s web-page have beensuccessfully performed without an error. The webpageof assignment and transportation method wasdesigned by using a functional model of aflowchart, which is implemented in theprogramming language of PHP.